Ethiopia’s agrifood system structure and drivers of transformation - Diao, Xinshen; Pauw, Karl; Thurlow, James; Ellis, Mia (International Food Policy Research Institute, 2023)
Ethiopia stands out as one of the fastest growing African countries between 2009 and 2019, with an average annual GDP growth rate close to 10 percent (ESS 2020). The global COVID-19 pandemic coupled with an armed civil conflict that started in November 2020 and continued for two years caused a significant slowdown in economic growth during the 2020–2022 period. Ethiopia’s GDP growth is now projected to recover to 5.3 percent in 2023 and 6.1 percent in 2024 (World Bank 2023), remaining well below the growth rates achieved in the pre-pandemic era. Agriculture remains an important sector in Ethiopia, accounting for one-third of GDP and two-thirds of jobs. The agriculture sector, like the broader economy, performed well prior to the pandemic and civil conflict, averaging 5.5 percent growth from 2009 to 2019 (ESS 2020), and played an important role in weathering the global commodity market shocks during 2022–2023 (Diao and Thurlow 2023). In this brief, we look beyond primary agriculture to understand how Ethiopia’s broader agrifood system (AFS) is contributing to growth and transformation in the country.